Efficient underwater acoustical localization method based on time difference and bearing measurements - Zhang, Liang; Zhang, Tao; Shin, Hyo-Sang; Xu, Xiang (IEEE, 2020)
This article addresses the underwater acoustical localization problem by using the time-difference-of-arrival (TDOA) and bearing-angle-of-arrival (BAOA) measurements. For the underwater acoustic equipment, such as the ultrashort baseline system (USBL), whose bearing measurements are different from the traditional angle-of-arrival (AOA) model, a closed-form solution for the hybrid TDOA/BAOA-based source localization problem is developed. However, the solution suffers from the measurement noise and cannot achieve the Cramer–Rao lower bound (CRLB) performance in the case of large measurement noise. Thus, an iterative constrained weighted least-squares method is presented to further minimize the error in the case of large noise. The CRLB for hybrid TDOA/BAOA source localization is analyzed, and the solution is proved to achieve the CRLB performance. Numerical simulations and field tests demonstrate that the proposed method outperforms the traditional methods in terms of estimation bias and accuracy. It can achieve the CRLB performance better.
Keywords: ultrashort baseline (USBL); time difference of arrival (TDOA); iterative constrained weighted least squares; Cramer–Rao lower bound (CRLB); Bearing angle of arrival (BAOA)